Solid electrolyte and method for producing same
A solid electrolyte with an argyrodite crystal structure and controlled diffraction peaks addresses hydrogen sulfide generation, ensuring high lithium ion conductivity and improved battery safety.
Patent Information
- Application Number
- JP2023505310
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-11
- Filing Date
- 2022-02-28
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2042-02-28
AI Technical Summary
The generation of hydrogen sulfide in sulfide solid electrolytes poses a challenge, especially in low dew point environments, which can compromise the safety and performance of solid-state batteries.
A solid electrolyte with a crystalline phase having an argyrodite crystal structure, composed of lithium, phosphorus, sulfur, and a halogen element, specifically bromine, is developed, with a controlled X-ray diffraction pattern featuring distinct peaks A1 and A2, ensuring high lithium ion conductivity while minimizing hydrogen sulfide generation.
The electrolyte effectively suppresses hydrogen sulfide generation while maintaining high lithium ion conductivity, enhancing the safety and performance of solid-state batteries.
Smart Images

Figure 0007602615000006 
Figure 0007602615000007 
Figure 0007602615000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid electrolyte and a method for producing the same, and also to an electrode mixture, a solid electrolyte layer, and a battery each containing a solid electrolyte. [Background technology]
[0002] In recent years, solid electrolytes have been attracting attention as an alternative to the electrolytes used in many liquid batteries. Solid-state batteries using solid electrolytes are safer than liquid batteries using flammable organic solvents, and are expected to be put to practical use as batteries with high energy density. As solid electrolytes, for example, sulfide solid electrolytes containing lithium (Li), phosphorus (P), sulfur (S), and halogen elements have been proposed (Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] US2016 / 156064A1 [Patent Document 2] US2019 / 148769A1 Summary of the Invention
[0004] A sulfide solid electrolyte may generate hydrogen sulfide in a low dew point environment such as a dry room. Therefore, an object of the present invention is to provide a solid electrolyte in which generation of hydrogen sulfide is suppressed.
[0005] The present invention includes lithium (Li), phosphorus (P), sulfur (S) and halogen (X) elements, The halogen (X) element includes at least a bromine (Br) element, Contains a crystalline phase having an argyrodite-type crystal structure, In the X-ray diffraction pattern measured by an X-ray diffractometer (XRD) using Cukα1 as a radiation source, peak A is present in the range of 2θ=25.2±1.0°, The peak A is separated into two peaks, peak A1 and peak A2, by a waveform separation operation, and the intensity of the peak A1 is expressed as I A1 , the intensity of the peak A2 is I A2 When the above I A1 Regarding I A2 The ratio (I A2 / I A1 ) is 0.37 or more, The half-width of the peak A1 is W A1 , the half-width of the peak A2 is W A2 When the above W A1 For the above W A2 Ratio (W A2 / W A1 ) is 3.2 or more. [Brief description of the drawings]
[0006] [Figure 1] FIG. 1 is a flow chart of the waveform separation operation of diffraction peaks. [Diagram 2] FIG. 2 is a diagram showing the results of waveform separation of the diffraction peaks of the solid electrolyte obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The present invention will be described below based on its preferred embodiments. The solid electrolyte of the present invention is made of a crystalline substance containing a crystal phase having an argyrodite-type crystal structure. The argyrodite-type crystal structure is a crystal structure possessed by a group of compounds derived from a mineral represented by the chemical formula: Ag8GeS6. The solid electrolyte of the present invention preferably has a crystal phase having an argyrodite-type crystal structure, since the lithium ion conductivity of the solid electrolyte is increased by the crystal phase having an argyrodite-type crystal structure. Whether or not the solid electrolyte of the present invention has a crystal phase having an argyrodite-type crystal structure can be confirmed by measurement using an X-ray diffraction device (XRD) or the like.
[0008] The solid electrolyte of the present invention contains a crystalline phase of an argyrodite-type crystal structure, and further contains lithium (Li), phosphorus (P), sulfur (S) and halogen (X) as constituent elements. The X-ray diffraction pattern derived from the crystalline phase of the argyrodite-type crystal structure differs depending on the composition of the crystalline phase, and when the solid electrolyte of the present invention contains the above-mentioned elements, the X-ray diffraction pattern measured by XRD using Cukα1 as a radiation source has a characteristic peak A derived from the crystalline phase of the argyrodite-type crystal structure in the range of 2θ=25.2±1.0°. In addition to this peak A, the solid electrolyte of the present invention may also exhibit peaks in the ranges of 2θ=15.3°±1.0°, 17.7°±1.0°, 30.0°±1.0°, 30.9°±1.0°, and 44.3°±1.0°. Furthermore, depending on the composition of elements constituting the solid electrolyte, the solid electrolyte of the present invention may exhibit peaks in the ranges of 2θ=47.2°±1.0°, 51.7°±1.0°, 58.3°±1.0°, 60.7°±1.0°, 61.5°±1.0°, 70.4°±1.0°, and 72.6°±1.0°, in addition to the above-mentioned diffraction peaks. For identification of peaks derived from the argyrodite-type crystal structure, for example, data of PDF No. 00-034-0688 can be used.
[0009] In the present invention, when peak A observed in the range of 2θ=25.2±1.0° is separated into two peaks, peak A1 and peak A2, by waveform separation, it is preferable that peak A1 and peak A2 satisfy the relationship described below from the viewpoint of effectively suppressing the generation of hydrogen sulfide while maintaining high lithium ion conductivity. The reason why the diffraction peak observed in the range of 2θ=25.2±1.0° is selected as the target diffraction peak is that within this range, accurate peak separation is possible without being affected by diffraction peaks of impurities, etc.
[0010] The fact that the peak A is separated into peak A1 and peak A2 by the waveform separation operation means that the solid electrolyte of the present invention contains other crystal phases in addition to the crystal phase of the Argyrodite-type crystal structure. In the solid electrolyte of the present invention, the crystal phase of the Argyrodite-type crystal structure is preferably the main phase. In the present invention, of the peaks A1 and A2, the peak with a relatively high intensity is peak A1 derived from the crystal phase of the Argyrodite-type crystal structure. On the other hand, the peak with a relatively low intensity is peak A2 derived from a crystal phase other than the crystal phase of the Argyrodite-type crystal structure. The degree of the presence of other crystal phases in the solid electrolyte of the present invention can be evaluated by the peak intensity and the half-width. Regarding the peak intensities, it can be determined that the greater the ratio of the intensity of peak A2 to the intensity of peak A1, the greater the presence ratio of other crystal phases. Regarding the half-width, it can be determined that the greater the ratio of the half-width of peak A2 to the half-width of peak A1, the lower the crystallinity of the other crystal phases.
[0011] The "main phase" refers to the phase that is the largest in proportion to the total amount of all crystal phases that constitute the solid electrolyte. Therefore, the content of the crystal phase of the argyrodite crystal structure contained in the solid electrolyte is preferably, for example, 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, and even more preferably 90% by mass or more, to the total amount of all crystal phases that constitute the solid electrolyte. The proportion of the crystal phase can be confirmed, for example, by XRD.
[0012] It is preferable that the intensities of peak A1 and peak A2 satisfy the following formula (1). I A2 / I A1 ≧0.37 (1) In formula (1), I A1 represents the peak intensity of peak A1, and I A2 represents the peak intensity of peak A2. In this specification, the peak intensity refers to the peak height from the baseline in the XRD diffraction pattern. A1 I A2The ratio (I A2 / I A1 A solid electrolyte in which the ratio of the charge carrier to the charge carrier is such that the charge carrier is a charge carrier having a high charge carrier and a low ... A2 / I A1 The value is more preferably 0.40 or more, and even more preferably 0.43 or more. I A2 / I A1 The value of I is set from the viewpoint of ensuring sufficient lithium ion conductivity to function as a solid electrolyte while maintaining the effect of suppressing the generation of hydrogen sulfide. A2 / I A1 It is preferable that I is ≦1.40. A2 / I A1 The value is more preferably 1.00 or less, and even more preferably 0.60 or less.
[0013] It is preferable that the half widths of the peaks A1 and A2 satisfy the following formula (2). W A2 / W A1 ≧3.2 (2) In equation (2), W A1 represents the half-width of peak A1, and W A2 W represents the half-width of peak A2. A1 W for A2 Ratio (W A2 / W A1 A solid electrolyte in which the ratio of the charge carrier to the charge carrier is such that the charge carrier is a charge carrier having a high charge carrier and a low charge carrier, and ... A2 / W A1 The value is more preferably 3.4 or more, and even more preferably 3.6 or more. W A2 / W A1 The value of W is set from the viewpoint of ensuring sufficient lithium ion conductivity to function as a solid electrolyte for other crystal structures from which peak A2 originates. A2 / W A1It is preferable that W is ≦15.0. A2 / W A1 The value is more preferably 10.0 or less, and even more preferably 7.0 or less.
[0014] Both peak A1 and peak A2 are observed at 2θ=25.2±1.0°. The peak top position of peak A1 and the peak top position of peak A2 are approximately the same position, and the difference between them is preferably within 0.5°, particularly preferably within 0.1°, from the viewpoint of effectively suppressing the generation of hydrogen sulfide while maintaining high lithium ion conductivity.
[0015] In order for the solid electrolyte of the present invention to satisfy the above formulas (1) and (2), the solid electrolyte may be produced, for example, by the method described below.
[0016] The inventors have found through their investigations that in the waveform separation of diffraction peaks, highly accurate waveform separation can be performed by approximating peak A1, which is the main peak, with a Gaussian function and peak A2, which is a peak derived from a crystal phase other than the argyrodite-type crystal structure, with an asymmetric double sigmoid function.
[0017] Gaussian Function y g is expressed by the following formula (3). g is a constant corresponding to the peak intensity, x cg is a constant representing the peak position, and w g is a constant corresponding to the peak width.
[0018]
number
[0019] Asymmetric Double Sigmoidal Function y s is expressed by the following formula (4). sis a constant corresponding to the peak intensity, and x cs is a constant representing the peak position, and w 1s is a constant corresponding to the peak width, and w 2s and w 3s is a constant corresponding to the bias of the peak width.
[0020]
number
[0021] Waveform separation of diffraction peaks and curve fitting can be performed using appropriate software, etc. One example is the least squares method using the solver function of Excel (Microsoft), which is a spreadsheet software. Specifically, fitting is performed by minimizing the reliability factor R expressed by the following formula (5) with the GRG nonlinearity using the solver function. I(2θ) in formula (5) indicates the signal intensity of the actual data. Also, P(2θ) in formula (5) is the fitting curve. Specifically, as shown in formula (6), the Gaussian function y g , the asymmetric double sigmoid function y corresponding to peak A2 s , and a constant y0 corresponding to the baseline. The range of the diffraction angle 2θ when calculating the reliability factor R can be any range that includes the diffraction peaks observed in the range of 2θ=25.2±1.0°. For example, it can be set to a range of 23.0° to 27.0°. The fitting parameters are the constant A for the Gaussian function of peak A1 expressed by equation (3). g , x cg , W g , and the constant A for the asymmetric double sigmoid function of peak A2 expressed by equation (4) s , x cs , W 1s , W 2s , W 3sand a baseline y0 is used. Curve fitting is judged to have converged only when the R factor is 20% or less, and if the R factor diverges or becomes greater than 20%, proceed to the next step.
[0022]
number
[0023]
number
[0024] A specific waveform separation operation of the diffraction peaks is performed according to the flowchart shown in Figure 1. This flowchart will be described in detail below.
[0025] First, in step 1, the parameter A for the Gaussian function of peak A1 expressed by equation (3) is g , x cg , W g , and the parameter A for the asymmetric double sigmoid function of peak A2 expressed by equation (4) s , x cs , W 1s , W 2s , W 3s Curve fitting is performed using the initial values shown in the figure. When the R factor converges in the curve fitting, the analysis ends there, and peaks A1 and A2 are determined.
[0026] The definitions of terms in Figure 1 are as follows: The "actual data peak intensity" refers to the value obtained by subtracting the baseline from the height of the signal at the apex of the most intense peak among the diffraction peaks observed in the range of 2θ=25.2±1.0°. The "actual data peak position" refers to the value of the diffraction angle 2θ at the apex signal of the most intense peak among the diffraction peaks observed in the range of 2θ=25.2±1.0°. "Actual data half-width" refers to the absolute value of the difference in diffraction angle 2θ at the signal whose intensity is 1 / 2 of the actual data peak intensity after excluding the baseline in the diffraction peak observed in the range of 2θ = 25.2 ± 1.0°. Note that when there are three or more diffraction angles 2θ at the signal whose intensity is 1 / 2 of the actual data peak intensity, the difference between the two points of the closest signal on the high-angle side and the closest signal on the low-angle side of the actual data peak position is taken. "Actual data 1 / 4 value width" refers to the absolute value of the difference in diffraction angle 2θ at the signal whose intensity is 1 / 4 of the actual data peak intensity after excluding the baseline in the diffraction peak observed in the range of 2θ = 25.2 ± 1.0°. Note that when there are three or more diffraction angles 2θ at the signal whose intensity is 1 / 4 of the actual data peak intensity, the difference between the two points of the closest signal on the high angle side and the closest signal on the low angle side of the actual data peak position is taken.
[0027] If the R-factor does not converge in step 1, proceed to step 2, change the initial value according to the rules shown in Figure 1, and perform curve fitting again. If the R-factor in curve fitting converges, the analysis ends there, and peaks A1 and A2 are determined. If the R-factor does not converge in step 2, proceed to step 3, where the initial value is further changed according to the rules shown in Figure 1 and curve fitting is performed again. If the R-factor in curve fitting converges, the analysis ends there and peaks A1 and A2 are determined. If the R-factor does not converge even in step 3, proceed to step 4, where the initial value is further changed according to the rules shown in Figure 1 and curve fitting is performed again. If the R-factor in curve fitting converges, the analysis ends there and peaks A1 and A2 are determined. If the R-factor in curve fitting does not converge, it is determined that curve fitting using the Gaussian function and asymmetric double sigmoid function is impossible, and curve fitting is performed using only the Gaussian function to determine only peak A1. The intensity of peak A2 is determined to be 0.
[0028] An example of the waveform separation result thus obtained is shown in Fig. 2. Fig. 2 shows the result of waveform separation of the diffraction peak of the solid electrolyte obtained in Example 1. As shown in the figure, the diffraction peak A is separated into a peak A1 approximated by a Gaussian function and a peak A2 approximated by an asymmetric double sigmoid function. Function y representing peak A1 obtained by curve fitting g Using the peak intensity I A1 and half width W A1 Specifically, the function y g The highest value among them is the peak intensity I A1 and the intensity is I A1 The difference between the diffraction angles 2θ at two points where the half-width W A1 Similarly, the function y s Using the peak intensity I A2 and half width W A2 Specifically, the function y s The highest value among them is the peak intensity I A2 and the intensity is I A2 The difference between the diffraction angles 2θ at two points where the half-width W A2 Let us assume that.
[0029] In the present invention, in order to achieve higher lithium ion conductivity and more effectively suppress the generation of hydrogen sulfide, it is advantageous to control the composition of the constituent elements of the solid electrolyte. Specifically, it is preferable to set the molar ratio of X element to P element, X / P, to 1.0 or more and 3.0 or less. In particular, it is preferable to set the molar ratio of X / P to 1.2 or more and 2.8 or less, and more preferably to 1.3 or more and 2.5 or less.
[0030] Regarding the composition of the constituent elements in the solid electrolyte, it is also advantageous to control the molar ratio of S element to P element. Specifically, it is preferable to set the molar ratio of S element to P element, S / P, to 3.0 or more and 5.0 or less. In particular, it is preferable to set the S / P molar ratio to 3.5 or more and 4.8 or less, and particularly 4.0 or more and 4.5 or less, since the lithium ion conductivity of the solid electrolyte is further increased and the generation of hydrogen sulfide is further effectively suppressed.
[0031] Furthermore, regarding the composition of the constituent elements in the solid electrolyte, it is preferable that the solid electrolyte contains at least Br element as the X element, since the lithium ion conductivity of the solid electrolyte is further increased and the generation of hydrogen sulfide is more effectively suppressed. The ratio (mol%) of Br element in the X element is, for example, preferably 50% or more, more preferably 60% or more, more preferably 70% or more, 80% or more, and even more preferably 90% or more. The ratio of Br element may be 100%. That is, the X element may contain only Br element. When the solid electrolyte contains other X elements in addition to Br element as X element, examples of the other X elements include chlorine (Cl), fluorine (F) and iodine (I), and it is particularly preferable to use Cl element.
[0032] The solid electrolyte of the present invention has the composition formula Li a It is preferable that the solid electrolyte be represented by PSbXc (X is a halogen element including at least Br element) from the viewpoint of enhancing the lithium ion conductivity of the solid electrolyte.
[0033] In the above composition formula, a, which indicates the molar ratio of lithium element, is, for example, preferably a number from 3.0 to 6.5, more preferably a number from 3.2 to 6.5, and even more preferably a number from 3.4 to 6.5. In the above composition formula, b, which indicates the molar ratio of sulfur element, is, for example, preferably a number from 3.5 to 4.8, more preferably a number from 3.8 to 4.6, and even more preferably a number from 4.0 to 4.6. In the above composition formula, c is, for example, preferably a number from 0.1 to 3.0, more preferably a number from 0.2 to 2.8, and even more preferably a number from 0.4 to 2.5. A solid electrolyte having a composition in which a, b, and c fall within these ranges has sufficiently high lithium ion conductivity.
[0034] The solid electrolyte of the present invention may contain elements other than Li, P, S, and X. For example, it may be possible to replace a part of the Li element with another alkali metal element, to replace a part of the P element with another pnictogen element, or to replace a part of the S element with another chalcogen element.
[0035] The solid electrolyte of the present invention has lithium ion conductivity in a solid state. The solid electrolyte of the present invention preferably has a lithium ion conductivity of, for example, 0.5 mS / cm or more, particularly 1.0 mS / cm or more, particularly 1.5 mS / cm or more, and particularly 1.7 mS / cm or more at room temperature, i.e., 25° C. The lithium ion conductivity can be measured using the method described in the Examples below.
[0036] The solid electrolyte of the present invention is preferably made of a powder as an aggregate of particles. The particle size of the solid electrolyte of the present invention is measured by a volume cumulative particle size distribution measurement method using a laser diffraction scattering type particle size distribution measurement method at a cumulative volume of 50% by volume, 50 The volume cumulative particle diameter D is preferably 10 μm or less, more preferably 8.0 μm or less, and particularly preferably 7.0 μm or less. 50 is preferably 0.1 μm or more, more preferably 0.3 μm or more, and particularly preferably 0.5 μm or more. By setting the particle size within this range, the contact points and contact area between the particles of the solid electrolyte are increased, and the lithium ion conductivity can be effectively improved. In addition, since the specific surface area is not excessively large, the generation of hydrogen sulfide can be effectively suppressed.
[0037] The solid electrolyte of the present invention can be preferably produced by the method described below. As the raw materials, a Li element source, a P element source, an S element source, and a Br element source are used. As the Li element source, for example, lithium sulfide (Li2S) can be used. As the P element source, for example, diphosphorus pentasulfide (P2S5) can be used. As the S element source, when the Li element source and / or the P element source is a sulfide, the sulfide can be used as the S element source. As the Br element source, lithium bromide can be used. These raw materials are mixed so that the Li element, the P element, the S element, and the Br element are in a predetermined molar ratio, and the resulting raw material composition is pulverized. Then, the pulverized raw material composition is fired under an inert gas atmosphere or fired under an atmosphere containing hydrogen sulfide gas.
[0038] In particular, in this manufacturing method, the particle size and crystal structure of the raw material composition are controlled to successfully manufacture the desired solid electrolyte. In particular, it is advantageous to appropriately adjust the operating conditions of the media mill used for mixing and grinding the raw material composition to suppress the raw materials from agglomerating and compounding with each other to grow into particles, and to keep the particle size of the raw materials relatively small. It is also advantageous to appropriately adjust the operating conditions of the media mill used for mixing and grinding the raw material composition to ensure that the crystal structure derived from the raw materials remains without generating a glass body or an argyrodite-type crystal structure. By doing so, the solid-phase reaction of the raw material composition can be made to proceed non-uniformly in the firing step described below. As a result, a solid electrolyte in which peak A, which can be separated into the above-mentioned peaks A1 and A2, is observed, can be easily obtained. In addition, by not grinding excessively, the crystallite size of the compound having the argyrodite-type crystal structure obtained in the firing step described below is prevented from becoming excessively large, and further, since it is not necessary to apply excessive grinding energy in the grinding step described below, the exposure of unstable new faces is suppressed, and the generation of hydrogen sulfide is suppressed.
[0039] It is preferable to use a media mill such as a bead mill or a ball mill for mixing and grinding the raw material composition. The energy applied during grinding is preferably such that the raw material composition is pulverized but a mechanochemical reaction does not occur. The table rotation speed of the media mill is, for example, preferably 500 rpm or less, more preferably 400 rpm or less, and even more preferably 300 rpm or less. The processing time of the media mill is, for example, preferably 5 minutes or more, and preferably 30 minutes or more. On the other hand, the above processing time is, for example, preferably 15 hours or less, more preferably 12 hours or less, and even more preferably 10 hours or less.
[0040] After the mixing and grinding of the raw material composition is completed in this manner, the raw material composition is then fired. The firing is preferably performed under an inert gas atmosphere such as nitrogen gas, or under an atmosphere containing hydrogen sulfide gas. The atmosphere containing hydrogen sulfide gas may be 100% hydrogen sulfide gas, or may be a mixed gas of hydrogen sulfide gas and an inert gas such as argon. Among them, an inert gas atmosphere such as nitrogen gas is more preferable. By lowering the sulfur partial pressure in the atmosphere, the solid-phase reaction in the raw material composition is less likely to proceed, and the generation of the argyrodite-type crystal structure can be made non-uniform, thereby making it possible to easily obtain a solid electrolyte in which peak A, which can be separated into the above-mentioned peaks A1 and A2, is observed. Also, from an industrial point of view, it is preferable to perform firing in an inert gas atmosphere, which is easy to handle. The firing temperature is, for example, preferably 350° C. or higher, more preferably 420° C. or higher, and even more preferably 470° C. or higher. On the other hand, the firing temperature is, for example, preferably 600° C. or lower, more preferably 550° C. or lower, and even more preferably 520° C. or lower. The firing time is preferably, for example, 0.5 hours, and more preferably 2 hours or more. On the other hand, the firing time is preferably, for example, 20 hours or less, and more preferably 10 hours or less, and even more preferably 5 hours or less, because a solid electrolyte containing a crystal phase having an argyrodite-type crystal structure can be suitably obtained.
[0041] The fired product thus obtained is subjected to a predetermined pulverization process. When the fired product is pulverized, either dry pulverization or wet pulverization may be performed, or both may be combined. The fired product obtained by mixing and pulverizing the raw material composition described above and firing is a composite of a plurality of argyrodite-type crystal structure compounds having different composition ratios and crystallinity due to the non-uniform solid-phase reaction. Due to this, there are more crystal grain boundaries compared to the fired product produced by the uniform solid-phase reaction, and the desired particle size can be obtained even with less pulverization energy in the pulverization process of the fired product. As a result, according to this manufacturing method, the generation of defects in the argyrodite-type crystal structure is suppressed. As a result, reactivity with moisture is suppressed, and solid electrolyte particles with less hydrogen sulfide generation can be easily obtained. In addition, according to this manufacturing method, since there are many crystal grain boundaries in the fired product, the proportion of highly reactive newly formed surfaces exposed in the pulverization process can be reduced, and from this viewpoint, the generation of hydrogen sulfide is also suppressed.
[0042] From the viewpoint of causing the above-mentioned heterogeneous solid-phase reaction, it is more desirable to adopt, as the X element constituting the solid electrolyte, Br element or I element, which has a relatively low melting point as a raw material and can cause a solid-phase reaction with less thermal energy, compared with Cl element, which has a high melting point as a raw material and requires a large amount of thermal energy for a solid-phase reaction. On the other hand, from the viewpoint of improving the ionic conductivity of a solid electrolyte containing a crystal phase having an argyrodite-type crystal structure, it is more desirable to employ Cl element or Br element. Considering the above, in order to fully exert the effects of the present invention, it is particularly desirable to use Br element alone or two kinds of elements, Br element and Cl element, as the X element constituting the solid electrolyte.
[0043] The solid electrolyte obtained by the above method can be used as a material constituting a solid electrolyte layer, a positive electrode layer, or a negative electrode layer. Specifically, the solid electrolyte of the present invention can be used in a battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer. That is, the solid electrolyte can be used in a so-called solid battery. More specifically, it can be used in a lithium solid battery. The lithium solid battery may be a primary battery or a secondary battery. There is no particular restriction on the shape of the battery, and for example, a laminate type, a cylindrical type, a square type, or the like can be adopted. The term "solid battery" includes a solid battery that does not contain any liquid or gel substance as an electrolyte, as well as an embodiment that contains, for example, 50 mass % or less, 30 mass % or less, or 10 mass % or less of a liquid or gel substance as an electrolyte.
[0044] When the solid electrolyte layer contains the solid electrolyte of the present invention, the solid electrolyte layer can be produced by, for example, a method of dropping a slurry consisting of a solid electrolyte, a binder, and a solvent onto a substrate and scraping it off with a doctor blade or the like, a method of contacting the substrate with the slurry and then cutting it with an air knife, a method of forming a coating film by a screen printing method or the like and then removing the solvent by heating and drying, etc. Alternatively, the solid electrolyte can also be produced by forming a powdered solid electrolyte into a compressed powder by pressing or the like and then appropriately processing it. From the viewpoint of the balance between short circuit prevention and volumetric capacity density, the thickness of the solid electrolyte layer is typically preferably 5 μm or more and 300 μm or less, and more preferably 10 μm or more and 100 μm or less.
[0045] The solid electrolyte of the present invention is used together with an active material to form an electrode mixture. The ratio of the solid electrolyte in the electrode mixture is typically 10% by mass or more and 50% by mass or less. The electrode mixture may contain other materials such as a conductive assistant and a binder as necessary. An electrode layer such as a positive electrode layer and / or a negative electrode layer can be produced by mixing the electrode mixture with a solvent to prepare a paste, applying the paste to a current collector such as aluminum foil, and drying the paste.
[0046] As the positive electrode material constituting the positive electrode layer, a positive electrode material used as a positive electrode active material of a lithium ion battery can be appropriately used. For example, a positive electrode active material containing lithium, specifically, a spinel type lithium transition metal oxide and a lithium metal oxide having a layered structure, etc. can be mentioned. By using a high voltage positive electrode material as the positive electrode material, it is possible to improve the energy density. In addition to the positive electrode active material, the positive electrode material may contain a conductive material or other materials.
[0047] As the negative electrode material constituting the negative electrode layer, a negative electrode material used as a negative electrode active material in a lithium ion battery can be appropriately used. Since the solid electrolyte of the present invention is electrochemically stable, it can be used at a potential lower than lithium metal or a potential lower than lithium metal (about 0.1 V vs. Li + Carbonaceous materials such as graphite, artificial graphite, natural graphite, and non-graphitizable carbon (hard carbon), which are materials that are charged and discharged with a current of 0.1 wt. / Li, can be used as the negative electrode material. This can greatly improve the energy density of the solid-state battery. In addition, silicon or tin, which are promising high-capacity materials, can be used as the active material. In a battery using a general electrolyte, the electrolyte reacts with the active material during charging and discharging, causing corrosion on the active material surface, resulting in significant deterioration of the battery characteristics. In contrast to this, if the solid electrolyte of the present invention is used instead of the electrolyte and silicon or tin is used as the negative electrode active material, the above-mentioned corrosion reaction does not occur, and the durability of the battery can be improved. The negative electrode material may also contain a conductive material in addition to the negative electrode active material, or other materials. EXAMPLES
[0048] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.
[0049] Example 1 Li2S powder, P2S5 powder, and LiBr powder were weighed out so as to obtain the composition shown in Table 1 below. These powders were ground and mixed using a planetary ball mill (P-5 manufactured by Fritsch) to obtain a raw material composition. The obtained raw material composition was fired to obtain a fired product. The firing was performed using a tubular electric furnace. Nitrogen gas was circulated in the electric furnace during firing. The firing temperature was set to 500°C, and firing was performed for 4 hours. The fired product was pulverized using a ball mill to obtain the desired solid electrolyte powder. As a result of XRD measurement, it was confirmed that this powder had a crystal phase with an argyrodite type crystal structure.
[0050] [Examples 2 to 4] A solid electrolyte powder was obtained in the same manner as in Example 1, except that a raw material composition was prepared so as to have the composition shown in the following Table 1. This powder was confirmed to have a crystal phase with an argyrodite-type crystal structure.
[0051] Comparative Examples 1 to 3 Each raw material powder was prepared so as to have the composition shown in Table 1 below. As shown in the table, the raw material composition was ground under conditions in which the rotation speed of the planetary ball mill was higher and the time was longer than in the examples. As shown in the table, the raw material composition was fired under conditions at a lower temperature and for a longer time than in the examples. Except for these, the solid electrolyte powder was obtained in the same manner as in Example 1.
[0052] [XRD measurement] The solid electrolytes obtained in the examples and comparative examples were subjected to XRD measurement under the following conditions, and the waveform separation operation of the diffraction peaks was performed according to the flowchart shown in FIG. 1. The peak positions, I A2 / I A1 and W A2 / W A1 The results are shown in Table 1. Also, the results of waveform separation of the diffraction peaks of the solid electrolyte obtained in Example 1 are shown in FIG. XRD measurements were performed using the "Smart Lab" X-ray diffractometer manufactured by Rigaku Corporation. Measurement conditions were: no exposure to air, scanning axis: 2θ / θ, scanning range: 10° to 120°, step width: 0.02°, scanning speed: 1° / min. The X-ray source was CuKα1 ray using a Johansson crystal. A one-dimensional detector was used for detection. Measurements were performed so that the intensity at 21.3±1.0° was 100 to 700 counts. In addition, measurements were performed so that the maximum peak intensity at 10° to 120° was 1000 counts or more.
[0053] [Lithium ion conductivity] The lithium ion conductivity of the solid electrolytes obtained in the examples and comparative examples was measured by the following method, and the results are shown in Table 1 below. Each solid electrolyte was placed in a glove box filled with thoroughly dried argon gas (dew point -60°C or less) and cooled to approximately 6 t / cm. 2 A load of 10 ...
[0054] [Amount of hydrogen sulfide generated] The amounts of hydrogen sulfide generated from the solid electrolytes obtained in the Examples and Comparative Examples were measured by the following method, and the results are shown in Table 1 below. The solid electrolyte was weighed out in 2 mg portions in a glove box purged with thoroughly dried argon gas (dew point -60°C or less) and placed in a bag sealed with a laminate film. After that, the solid electrolyte was placed in a constant temperature and humidity chamber kept at room temperature (25°C) in an atmosphere with a dew point of -30°C adjusted by mixing dry air and atmospheric air, with a capacity of 1500 cm. 3A glass separable flask was placed in the flask. The separable flask was kept in a constant temperature and humidity chamber until the inside of the flask was identical to the environment inside the chamber, and then the sealed bag containing the solid electrolyte was opened inside the chamber, and the solid electrolyte was quickly placed inside the separable flask. A fan was placed inside the separable flask to prevent gas from accumulating, and the fan was rotated to stir the atmosphere inside the separable flask. The concentration of hydrogen sulfide generated from immediately after the separable flask was sealed until 30 minutes had elapsed was measured 30 minutes later using a hydrogen sulfide sensor (GX-2009 manufactured by Riken Keiki). The minimum measurement value of the hydrogen sulfide sensor is 0.1 ppm.
[0055] [Table 1]
[0056] As is clear from the results shown in Table 1, the solid electrolytes obtained in the examples have higher lithium ion conductivity and suppress the generation of hydrogen sulfide compared to the solid electrolytes of the comparative examples. [Industrial Applicability]
[0057] According to the present invention, there is provided a solid electrolyte in which generation of hydrogen sulfide is suppressed.
Claims
1. Contains lithium (Li), phosphorus (P), sulfur (S) and halogen (X), The halogen (X) element includes at least a bromine (Br) element, Contains a crystalline phase having an argyrodite-type crystal structure, In an X-ray diffraction pattern measured by an X-ray diffractometer (XRD) using Cukα1 as a radiation source, the X-ray diffraction pattern has a peak A in the range of 2θ=25.2±1.0°, The peak A is separated into two peaks, peak A1 and peak A2, by a waveform separation operation, and the intensity of the peak A1 is I A1 , the intensity of the peak A2 is I A2 When the above I A1 The above I A2 The ratio (I A2 / I A1 ) is 0.37 or more; The half-width of the peak A1 is W A1 , the half-width of the peak A2 is W A2 When the above W A1 The above W A2 The ratio (W A2 / W A1 ) is 3.2 or more.
2. 2. The solid electrolyte according to claim 1, wherein a molar ratio (Br / X) of said bromine (Br) element to said halogen (X) element is 0.5 or more.
3. a molar ratio (X / P) of the halogen (X) element to the phosphorus (P) element is 1.0 or more and 3.0 or less; 3. The solid electrolyte according to claim 1, wherein a molar ratio (S / P) of the sulfur (S) element to the phosphorus (P) element is 3.0 or more and 5.0 or less.
4. I A1 The above I A2 The ratio (I A2 / I A1 4. The solid electrolyte according to claim 1 , wherein the σ is 1.40 or less.
5. The W A1 The above W A2 The ratio (W A2 / W A1 5. The solid electrolyte according to claim 1 , wherein the σ is 15.0 or less.
6. An electrode mixture comprising the solid electrolyte according to claim 1 and an active material.
7. A solid electrolyte layer comprising the solid electrolyte according to claim 1 .
8. A battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, the battery containing the solid electrolyte according to claim 1 .
Citation Information
Patent Citations
Sulfide-Based Solid Electrolyte for Lithium Ion Battery
US20160156064A1
Solid electrolyte for all-solid lithium secondary battery, all-solid lithium secondary battery, and method of preparing the solid electrolyte
US20190148769A1
Sulfide solid electrolyte and battery
WO2020095936A1
